A note on money creation in emerging market economies. Issue 1 (3rd April 2017) - Ponomarenko, Alexey
Abstract : Purpose: This paper aims to discuss the money creation mechanisms in emerging markets with special focus on external transactions and outlines the implications for monetary policy and financial stability issues. Design/methodology/approach: To make the argument, the authors analyze a historical episode of flows of funds in Korea and Russia and conduct a canonical correlation analysis for a cross-section of emerging market economies. Findings: The authors show that changes in the net foreign assets of the banking system are associated with (or cause) deposits fluctuations. In emerging markets, however, the scope of such fluctuations is limited unless driven by changes in the foreign reserves of a central bank. Originality/value: Some preliminary implications for financial stability implementation may be drawn from this analysis. Introducing the net stable funding ratio requirement is unlikely to have any significant destabilizing effect on credit creation in emerging markets (in this regard, it is similar to the restriction on banks' foreign currency position, which is a common prudential measure). Instead, it is likely to trigger a balance of payment adjustment that is similar to that experienced by an economy during its transition from fixed to flexible exchange rate regime.